Complex patterns of transcription of a Drosophila retrotransposon in vivo and in vitro by RNA polymerases II and III. - Arkhipova, I R (1995)
The mdg1 retrovirus-like retrotransposon of Drosophila melanogaster was found to possess a complex promoter which can be transcribed by both RNA polymerases II and III (pol II and pol III). Pol III transcription, which is not typical of protein-coding genes, is driven by the sequences located in the long terminal repeat (LTR) of mdg1, predominantly within the transcribed region and is initiated 10 bp upstream from the regular pol II RNA start site. The pol III RNA start site is observed not only in in vitro transcription reactions, but also in total RNA isolated from tissue culture cells, larvae, pupae and adult flies. A possible role of pol III transcription in mechanisms controlling the expression of full-length mdg1-encoded transcripts in the developing fly, which are apparently relaxed in cell culture, is discussed.